Eugenic Selection Benefits Embryos - Walker, Mark (Bioethics, 2014)
The primary question to be addressed here is whether pre-implantation genetic diagnosis (PGD), used for both negative and positive trait selection, benefits potential supernumerary embryos. The phrase ‘potential supernumerary embryos’ is used to indicate that PGD is typically performed on a set of embryos, only some of which will be implanted. Prior to any testing, each embryo in the set is potentially supernumerary in the sense that it may not be selected for implantation. Those embryos that are not selected, and hence destroyed or frozen, are ‘actually supernumerary’. The argument to be advanced is hypothetical: If embryos may be said to benefit or be harmed by our actions, then PGD used to select for an embryo or embryos with the highest expected Wellbeing benefits potential supernumerary embryos. The argument shows that the ‘non-identity’ problem is not sufficient to show that eugenic selection does not benefit supernumerary embryos.